DETERMINE THE LOCATION OF NODES IN WIRELESS SENSOR NETWORK BY USING GENETIC ALGORITHM (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Wireless sensor networks (WSNs) are widely used in the modern world. An important requirement for the optimal operation of the network is the determination of the location of the sensor nodes. When building the network, various positioning methods are used, providing the necessary level of accuracy in determining the location of the sensor nodes. It makes it possible to adjust the transmission power of the nodes, to determine which sensors should be in standby mode and which ones to be in working mode, and also to determine the best route for transmitting information. The Angle of Arrival (AoA) method is a method of positioning with respect to the location of the mobile station, which is determined by triangulation of received information collected at multiple access points. The Time of Arrival (ToA) method, also known as the telemetry method, provides one-way measurements of the time difference of signal propagation from the exact time the signal is sent by the transmitter and the exact time the signal is received at the receiver. The Time Difference of Arrival (TDoA) method is based on the concept that a mobile station transmits a message that has been received by at least three access points that are synchronized with other access points. Most of these methods involve approximation and/or linearization, which introduce additional errors. In the present work, an algorithm is proposed for calculating the location of the sensor nodes by the ToA method using a genetic algorithm (GA). An objective function is derived, based on the distances from the reference nodes and the mobile sensor node whose location is sought. This objective function is minimized using a GA, resulting in the desired node coordinates. Investigations of the accuracy of determining the location of the sensor nodes at different accuracy of distance measurement have been made.